Examining the ‘ideal’ and ‘actual’ characteristics of university academics: perceptions and experiences of prospective teachers in Tanzania - Kavenuke, Patrick Severine (Papers in Education and Development, 2024)
Examining the “ideal” versus “actual” characteristics of university lecturers is a crucial focus in higher education research. This study explored prospective teachers’ perceptions of the “ideal” characteristics of university lecturers while uncovering their experiences with the “actual” characteristics observed in practice. The study employed a qualitative approach using a single case study design with a sample size of 26 participants. Regarding “ideal” characteristics, findings indicated that university lecturers should be friendly, maintain good relationships with prospective teachers, be role models and advisors, be creative and reflective, and be competent in pedagogical content knowledge. Mixed results were found on the “actual” university lecturers’ characteristics, revealing that while some lecturers exhibited negative traits such as being less competent, unkind, and authoritarian, others demonstrated positive qualities, including competence, approachability, and friendliness as advisors to prospective teachers. The study concludes that university lecturers must strive to cultivate positive traits within themselves to ensure the smooth teaching and learning of prospective teachers.